Crafting the 613 Commandments : Maimonides on the Enumeration, Classification and Formulation of the Scriptural Commandments. - Friedberg, Albert (Holocaust (Boston, Mass.), 2012)
Rabbinic tradition has it that 613 commandments were given to Moses on Mount Sinai, but it does not specify those included in the enumeration. Maimonides methodically and artfully crafts a list of 613 commandments in a work that serves as a prolegemenon to the Mishneh Torah, his monumental code of law. This book explores the surprising way Maimonides put this tradition to use and his possible rationale for using such a tradition. It also explores many of the philosophical and ethical ideas animating the composition of such a list. In the book's second half, Friedberg examines the manner by which Maimonides formulated positive commandments in the Mishneh Torah, leading him to suggest new dimensions in Maimonides' legal theory.